2018
DOI: 10.1353/hpn.2018.0009
|View full text |Cite
|
Sign up to set email alerts
|

Meeting Student Needs: Integrating Spanish Heritage Language Learners into the Second Language Classroom

Abstract: Despite the increase of Spanish heritage language (HL) courses in response to the linguistic needs of HL learners, these courses often combine this student population with advanced second language (L2) learners. This common scenario presents a challenge to many instructors who lack the training to negotiate intercultural and linguistic issues in the classroom so that all students can benefit. This essay presents key intercultural concerns (e.g., embarrassment and intimidation) and suggests strategies for instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…It has been identified that there are, indeed, several students who are NES and HLS of English significant enough to raise a potential hindrance in the ELT field in Ecuador. As mentioned in Burgo (2018), countries such as the USA have created special courses for students who are HLS of Spanish so that better teaching work can be done with that specific group of students. In the same study, a problem that has been identified is that many NES and HLS are placed in advanced language classes with L2 learners -as is the case of a high school that works their students by English levels.…”
Section: Discussionmentioning
confidence: 99%
“…It has been identified that there are, indeed, several students who are NES and HLS of English significant enough to raise a potential hindrance in the ELT field in Ecuador. As mentioned in Burgo (2018), countries such as the USA have created special courses for students who are HLS of Spanish so that better teaching work can be done with that specific group of students. In the same study, a problem that has been identified is that many NES and HLS are placed in advanced language classes with L2 learners -as is the case of a high school that works their students by English levels.…”
Section: Discussionmentioning
confidence: 99%
“…The first reason is that SSP courses and programs are aimed at adult students preferably with a general base of language proficiency, since this is necessary to be able to develop communicative skills in specific professional contexts (Sánchez-López, 2012). The second reason behind this argument is the empowerment that the HLL receives from Spanish for the professions to be able to analyze specialized discourse and, as a specialist, to take responsibility for the development of their own learning outside the classroom (Upton, 2012;Burgo, 2017;Carreira, 2017). The third reason is the development of leadership skills in the Spanish class for the professions, particularly in service learning, regardless of profession or rank (Spaine Long, 2013;Uribe et al, 2014;Derby et al, 2014;Doyle, 2017).…”
Section: Spanish For Specific Purposes Leadership and Heritage Langmentioning
confidence: 99%
“…As already stated, even when there exist separate tracks for HLLs and L2 learners in college Spanish programs, all learners merge in the same advanced classes as the two tracks disappear (Burgo, 2017;Carreira, 2012Carreira, , 2017. This is true for all areas of study offered in the undergraduate major, such as literature, linguistics, culture, and more recently, Spanish for specific purposes (SSP) courses.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations